Identification of Two Flavonoids as New and Safe Inhibitors of Kynurenine Aminotransferase II via Computational and In Vitro Study - Redouane Rebai; Luc Jasmin; Abdennacer Boudah (Pharmaceuticals)
Background/Objectives: Kynurenine aminotransferase II (KAT-II) is a target for treating several diseases characterized by an excess of kynurenic acid (KYNA). Although KAT-II inactivators are available, they often lead to adverse side effects due to their irreversible inhibition mechanism. This study aimed to identify potent and safe inhibitors of KAT-II using computational and in vitro approaches. Methods: Virtual screening, MM/GBSA, and molecular dynamics simulations were conducted to identify the top drug candidates, followed by kinetic measurements and in vitro cytotoxicity evaluation. Results: The study showed that two compounds, herbacetin and (-)-Epicatechin exhibited the best scores. Their Glide docking scores are −8.66 kcal/mol and −8.16 kcal/mol, respectively, and their MM/GBSA binding energies are −50.30 kcal/mol and −51.35 kcal/mol, respectively. These scores are superior to those of the standard inhibitor, PF-04859989, which has docking scores of −7.12 kcal/mol and binding energy of −38.41 kcal/mol. ADMET analysis revealed that the selected compounds have favorable pharmacokinetic parameters, moderate bioavailability, and a safe toxicity profile, which supports their potential use. Further, the kinetic study showed that herbacetin and (-)-Epicatechin are reversible KAT-II inhibitors and exhibit a competitive inhibition mechanism. Their half-maximal inhibitory concentrations (IC50) are 5.98 ± 0.18 µM and 8.76 ± 0.76 µM, respectively. The MTT assay for cell toxicity indicated that the two compounds do not affect HepG2 cell viability at the necessary concentration for KAT-II inhibition. Conclusions: These results suggest that herbacetin and (-)-Epicatechin are suitable for KAT-II inhibition and are promising candidates for further development of KAT-II inhibitors.